Fenomena Social Shopping Pada Generasi Z - Nur Khobibah; Insan Permadi; Setyawan, Milvania Azlia Setyawan; Nisa, S.I.Kom., M.Si., Fitria Khairum Nisa (Fakultas Ilmu Komunikasi Universitas Islam Riau, 2023)
Social shopping is an activity to share consumer experiences in shopping online and offline. The phenomenon of social shopping is often seen on social media, where consumers share their experiences in consuming goods or services either through Instagram or Tiktok. This phenomenon is then utilized by potential consumers. When shopping online, consumers often look for product information through reviews from various sources, both online and from trusted people. The group is a reference group which is a reference group for finding information in shopping. Generation Z as digital natives born in the internet era tend to choose online shopping as the main shopping activity. This study aims to explain the phenomenon of social shopping in generation Z and elaborate on the factors that influence generation Z to do social shopping. The research method used qualitative methods by interviewing nine informants selected using purposive sampling techniques. Data analysis is carried out through the process of data reduction, data presentation and conclusions. The results showed that social shopping is a form of consumer concern for other consumers, in order to get true information before buying a product. This is because consumers who provide reviews also often look for information related to the products they will buy through reviews from others. So that social shopping becomes a circle of information search processes in online shopping.